Analisis Cerita Rakyat “Putri Pinang Gading” Sebagai Media Eksplorasi Budaya Anak Sekolah Dasar - Richieta Angeline (Penerbit dan Percetakan, CV. Picmotiv, 2024)
Indonesia has a very varied cultural richness, reflected in the various cultures, especially the number of folk tales that represent each region. The main problem of this research is that there are many folk tales that are less popular, even forgotten by society due to factors of contemporary development and globalization, one of which is the folk tale